Studies on Some Complexes of Cobalt (II) and Nickel(II) with bis-(2-Hydroxyimino-1-Phenyl Propylidene)-1,4-Diamino Benzene. - SAHU, K.; KUMARI, URMILA; CHANDRA YADAV, SHIV (Asian Journal of Chemistry, 2010)
A series of metal complexes of bis-(2-hydroxyimino-1-phenyl propylidene)-1,4-diamino benzene types M2L2·4H2O and M2(LH2)2x4 where M = Co(ll), Ni(II), X = Cl-, Br -, I- have been synthesised and characterised on the basis of elemental analyses, magnetic moment, infrared and electronic spectral data.